Tổng hợp vật liệu nano từ tính LaFeO3 bằng phương pháp sol-gel sử dụng lòng trắng trứng - Tiến, Nguyễn Anh; Minh Thúy, Nguyễn Thị (Vietnam Journal of Chemistry, 2015)
LaFeO3 perovskite nanomaterial has been synthesized by sol-gel method using egg whites through the hydrolysis of La(III) and Fe(III) cations in the boiling water. The results of DTA/TGA/DrTGA, XRD, SEM, TEM methods showed that uniform nanostructured LaFeO3 crystals with the particles size of 30 nm were obtained after calcination at 600 ºC. The magnetic characteristics of LaFeO3 material such as Mr, Ms, Hc decreased with the increasing of crystals size.